Indole-Induced Activities of β-Lactamase and Efflux Pump Confer Ampicillin Resistance in Pseudomonas putida KT2440 - Kim, Jisun; Shin, Bora; Park, Chulwoo; Park, Woojun (Frontiers in Microbiology, 2017)
Indole, which is widespread in microbial communities, has received attention because of its effects on bacterial physiology. Pseudomonas putida and Pseudomonas aeruginosa can acquire ampicillin (Amp) resistance during growth on indole-Amp agar. Transcriptome, mutant, and inhibitor studies have suggested that Amp resistance induced by indole can be attributed to increased gene expression of ttgAB encoding two genes of RND-type multidrug efflux operons and an ampC encoding β-lactamase. Expression, enzyme activities, and mutational analyses indicated that AmpC β -lactamase is important for acquiring Amp resistance of P. putida in the presence of indole. Here, we show, for the first time, that volatile indole increased Amp-resistant cells. Consistent with results of the volatile indole assay, a low concentration of indole in liquid culture promoted growth initially, but led to mutagenesis after indole was depleted, which could not be observed at high indole concentrations. Interestingly, ttgAB and ampC gene expression levels correlate with the concentration of indole, which might explain the low number of Amp-mutated cells in high indole concentrations. The expression levels of genes involved in mutagenesis, namely rpoS, recA, and mutS, were also modulated by indole. Our data indicates that indole reduces Amp-induced heterogeneity by promoting expression of TtgABC or MexAB-OprM efflux pumps and the indole-induced β-lactamase in P. putida and P. aeruginosa.